2009
DOI: 10.1542/peds.2008-1352
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine, Early Neonatal, and Postdischarge Growth and Neurodevelopmental Outcome at 5.4 Years in Extremely Preterm Infants After Intensive Neonatal Nutritional Support

Abstract: Growth from birth to discharge seemed to be associated with long-term motor development. Cognitive development was associated with intrauterine growth measured as weight at birth, early neonatal weight gain, and postdischarge head circumference growth. Improving particularly early neonatal growth may improve long-term outcome in extremely preterm infants, but the effects of improved growth may only be small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
306
5
28

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(356 citation statements)
references
References 41 publications
17
306
5
28
Order By: Relevance
“…7 Treatments such as mechanical ventilation may adversely affect cognitive development, 8 while nutritional support may help improve neurodevelopmental outcomes. 9 In contrast, a favorable early social environment including responsive parenting may stimulate cognitive development 10 and VP/VLBW infants are more affected by both favorable and unfavorable environments than term-born infants. 11 Unknown is which prenatal, perinatal, and neonatal factors most strongly predict adult cognitive abilities, thus the goal of this study was to investigate the combined and separate risks of pregnancy complications, neonatal morbidity, neonatal treatment, and early social environment on adult cognitive abilities in a large prospective sample of VP/VLBW individuals.…”
mentioning
confidence: 99%
“…7 Treatments such as mechanical ventilation may adversely affect cognitive development, 8 while nutritional support may help improve neurodevelopmental outcomes. 9 In contrast, a favorable early social environment including responsive parenting may stimulate cognitive development 10 and VP/VLBW infants are more affected by both favorable and unfavorable environments than term-born infants. 11 Unknown is which prenatal, perinatal, and neonatal factors most strongly predict adult cognitive abilities, thus the goal of this study was to investigate the combined and separate risks of pregnancy complications, neonatal morbidity, neonatal treatment, and early social environment on adult cognitive abilities in a large prospective sample of VP/VLBW individuals.…”
mentioning
confidence: 99%
“…23 When schoolchildren who had been very low birth weight preterms were assessed, it was observed that inadequate intrauterine growth had an effect on cognitive development, but not on motor development. 24 This variation between study results is probably because of differences in patient samples, methods and follow-up duration, but, in general, the data warn that small for gestational age premature infants have poor developmental prognosis, having been exposed to a situation of double risk: a reduced gestation period and intrauterine growth restriction.…”
Section: Resultsmentioning
confidence: 99%
“…In clinical studies, brain and cranial growth have been associated with subsequent neurodevelopment (5,39). A polymorphism in the IGF I promotor gene, which is known to regulate serum IGF I levels, has been related with slower cranial growth from birth until 5 y of age (40).…”
Section: The Role Of Igf I In Neurodevelopmentmentioning
confidence: 99%
“…Preterm birth and postnatal growth restriction have both been associated with impaired neurodevelopmental outcome (4). However, Franz et al found that only a small percentage of the variability, roughly 3%, of the mental processing composite score was explained by growth (5). There might be a common factor leading to both poor growth and poor neurodevelopment, e.g., a poor nutritional status or major neonatal morbidities.…”
mentioning
confidence: 99%
See 1 more Smart Citation